2023
DOI: 10.1039/d2ta09831h
|View full text |Cite
|
Sign up to set email alerts
|

Diatomic molecule catalysts toward synergistic electrocatalytic carbon dioxide reduction

Abstract: Synergistic catalysis with diatomic catalysts is an effective means to boost carbon dioxide (CO2) electroreduction efficiency and product selectivity; studies in this field also contribute to an atomic-level understanding of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Wang and coworkers designed a dual atom Co-salophen (Co-DAC) catalyst by using a non-covalent anchoring strategy to disperse Co on carbon nanotube (CNT) surfaces. 82 Uniform dispersion of Co dual atoms on CNTs was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), HAADF-STEM, and Raman spectroscopy (Fig. 5a).…”
Section: Carbon Monoxide: a Key Intermediate In C 2+ Product Formationmentioning
confidence: 99%
“…Wang and coworkers designed a dual atom Co-salophen (Co-DAC) catalyst by using a non-covalent anchoring strategy to disperse Co on carbon nanotube (CNT) surfaces. 82 Uniform dispersion of Co dual atoms on CNTs was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), HAADF-STEM, and Raman spectroscopy (Fig. 5a).…”
Section: Carbon Monoxide: a Key Intermediate In C 2+ Product Formationmentioning
confidence: 99%
“…Metallosalen/salophen (bis(salicylidene)ethylenediamine and bis(salicylidene)phenyldiamine) complexes have attracted considerable attention due to their versatile applications in catalysis [1][2][3][4][5][6][7][8][9][10], supramolecular chemistry [11][12][13][14][15][16][17][18], optical materials [19][20][21], and biological sensors or therapeutics [22,23] because of their rich chemistry and ease of manipulation of organic ligands. Among these complexes, zinc (II) salen/salophen complexes are of particular interest due to the non-redox nature and d 10 closed-shell configuration of the Zn 2+ ion, making them suitable for ligand-dependent fluorescent materials [24].…”
Section: Introductionmentioning
confidence: 99%
“…In order to complement the above‐mentioned deficiencies of SACs, diatomic in the field of electrochemical CO 2 RR [20] . Firstly, DACs as a continuation of the SACs family can somehow increase the loading of metal atomic centers exponentially [21] . Secondly, DACs can effectively break the linear relationship of the adsorption of SACs on each intermediate, thus making it easier to carry out multi‐electron reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Firstly, DACs as a continuation of the SACs family can somehow increase the loading of metal atomic centers exponentially. [21] Secondly, DACs can effectively break the linear relationship of the adsorption of SACs on each intermediate, thus making it easier to carry out multi-electron reactions. Preliminary studies have shown that DACs can achieve reaction pathways that are not accessible to SACs.…”
Section: Introductionmentioning
confidence: 99%